2023
DOI: 10.1039/d2bm01807a
|View full text |Cite
|
Sign up to set email alerts
|

Cationic phosphorus dendron nanomicelles deliver microRNA mimics and microRNA inhibitors for enhanced anti-inflammatory therapy of acute lung injury

Abstract: Development of efficient nanomedicines to repress the repolarization of M1 phenotype macrophages and therefore inhibit pro-inflammatory cytokine overexpression for anti-inflammatory therapy is still a challenging task. We report here an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Different nanoplatforms based on phosphorus dendrimers have been created as carriers for the delivery of genes or drugs due to their biological activities. The interaction of cationic phosphorus dendrimers with proteins has been described, while the necessity of depending on positive charge to deliver protein intracellularly needs to be reevaluated given that high densities of positive charge cause unpredictable cytotoxicity . Therefore, it is vital to develop efficient carriers based on anionic phosphorus dendrimers to effectively deliver functional proteins to exert synergistic and enhanced therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Different nanoplatforms based on phosphorus dendrimers have been created as carriers for the delivery of genes or drugs due to their biological activities. The interaction of cationic phosphorus dendrimers with proteins has been described, while the necessity of depending on positive charge to deliver protein intracellularly needs to be reevaluated given that high densities of positive charge cause unpredictable cytotoxicity . Therefore, it is vital to develop efficient carriers based on anionic phosphorus dendrimers to effectively deliver functional proteins to exert synergistic and enhanced therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy has been widely used to treat different diseases (e.g., cancer and infectious diseases) by transfecting exogenous genetic materials (e.g., plasmid DNA, mRNA, or short-interfering RNA) to target cells to result in the associated protein expression or gene silencing. Among the widely used genetic materials, microRNA (miR) has aroused extensive interest. As a kind of noncoding RNA, miRs are single-stranded endogenous small RNA having a length of about 20–24 nucleotides and can negatively regulate gene expression through translation inhibition and target mRNA degradation. , In cancer biology, miR deregulation is known to be involved in the occurrence of many types of cancer, and miR has been discovered to play a significant role in cell proliferation, ,, differentiation, angiogenesis, and apoptosis . Hence, the regulation of miR has been recognized as a compelling new therapeutic method to tackle cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus dendrimers or dendrons, due to their good biocompatibility and the presence of a large number of modifiable sites on the surface and branches, have been shown to have excellent performance in drug delivery, , gene transfection , and drug active per se . Their relatively convenient synthesis method also allows the development of various nanoparticulate systems to tackle a wide range of diseases. Our earlier work has shown that phosphorus dendrimers bearing pyrrolidinium or piperidinium on their surface can be used for gene delivery to treat breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, developing new therapeutic strategies to delay or even hinder the progression of IPF is highly desired. 6,7 Although the etiology of IPF is still unknown, repeated injury of alveolar epithelial cells is a recognized mechanism. 8 Several studies have confirmed the pathogenetic role of oxidative stress in IPF.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, due to the unclear pathogenesis of IPF, these two drugs have limited efficacy in halting disease progression and are often accompanied by toxic side effects, such as diarrhea, gastrointestinal reflux, and myocardial infarction . Therefore, developing new therapeutic strategies to delay or even hinder the progression of IPF is highly desired. , …”
Section: Introductionmentioning
confidence: 99%